Mikhail Bulgakov’s Childhood and Family Relationships in the Context of Contemporary Psychological Knowledge - Magdalena Jedrzejuk-Witek (Zeszyty Cyrylo-Metodiańskie)
The subject of the article is Mikhail Bulgakov’s (1891–1940) childhood and relationships in his family of origin. Although biographers generally perceive the writer’s childhood as a happy one, certain aspects of his life, such as his drug addiction or his consistent avoidance of the subject of his own childhood in his work, may prompt a revisionist view of this period in his life. This new perspective is further fostered by the ever-dynamic development of psychology and pedagogy, through which the role of childhood as a time in which the human psyche and personality are formed is more clearly recognised. In the context of Bulgakov, there is no doubt that especially the death of his father, Afanasiy Bulgakov, must have been a difficult experience for him as a teenage boy. Moreover, as the analysis shows, although the Bulgakov family was not lacking in joy and warmth, it was also not free of emotional problems that could have had an impact on both the writer’s future life and work. The results of this analysis shed new light on a seemingly thoroughly familiar figure of the author, and can thus provide a starting point for new, contemporary interpretations of his works.